2023
DOI: 10.1186/s12888-023-04672-5
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about sleep: links with ruminations, nightmare, and anxiety

Abstract: Objective Dysfunctional cognitions related to sleep play a major role in insomnia but also in nightmares. Moreover, they are closely related to anxiety. To our knowledge, no study has probed the impact of non-constructive ruminations on these dimensions in their harmful interplay with sleep. The aim of this study is to provide new insights into the processes underlying the dysfunctional cognitions-insomnia relationship. Method Four hundred twenty n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In exploring the mechanism through which anxiety influences sleep disorders, previous studies have demonstrated the mediating roles of bedtime procrastination, fear and rumination in the relationship between anxiety and sleep disorders ( Pace-Schott et al, 2015 ; Campbell and Bridges, 2023 ; Faccini et al, 2023 ). However, the role of positive psychological energy, such as flourishing, has often been ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In exploring the mechanism through which anxiety influences sleep disorders, previous studies have demonstrated the mediating roles of bedtime procrastination, fear and rumination in the relationship between anxiety and sleep disorders ( Pace-Schott et al, 2015 ; Campbell and Bridges, 2023 ; Faccini et al, 2023 ). However, the role of positive psychological energy, such as flourishing, has often been ignored.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that positive beliefs about rumination initiate rumination in depression [ 28 , 29 , 30 , 31 ], and the treatment of metacognition has been found to be effective in improving rumination in patients with social anxiety disorder [ 32 ]. Importantly, ruminations (16.6%) emerged as mediators of the relationship between dysfunctional beliefs and attitudes toward sleep and insomnia [ 33 ].…”
Section: Introductionmentioning
confidence: 99%